1994
DOI: 10.1213/00000539-199402000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Blood Volume Redistribution During Cross-Clamping of the Descending Aorta

Abstract: We tested the hypothesis that occlusion of the descending aorta is associated with blood volume redistribution resulting in a relative hypervolemia in organs and tissues proximal to the level of occlusion. The study was performed on splenectomized dogs anesthetized with pentobarbital. Whole body scintigraphy with a Sophy DSX rectangular large field of view gamma-camera equipped with a high resolution collimator was used; Tc99m was used to label plasma albumin. The aorta was occluded at diaphragmatic and suprar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
6

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 0 publications
1
14
0
6
Order By: Relevance
“…Data from animal models and from human research demonstrate that aortic occlusion, which is commonly performed by crossclamping the descending aorta for vascular control during aortic surgery, results in net flow diversion to the cerebral from the lower-extremity circulatory beds, thereby increasing cerebral blood flow. [707][708][709][710][711][712][713][714][715] This evidence generated the development of a catheter-based device with 2 balloons near its distal tip placed in the infrarenal and suprarenal positions in the descending aorta (NeuroFlo device; CoAxia, Maple Grove, MN). After insertion via the femoral artery, the balloons are inflated sequentially up to ≈70% of the diameter of the aortic lumen over a period of 45 minutes to an hour, followed by removal.…”
Section: Mechanical Flow Augmentationmentioning
confidence: 99%
“…Data from animal models and from human research demonstrate that aortic occlusion, which is commonly performed by crossclamping the descending aorta for vascular control during aortic surgery, results in net flow diversion to the cerebral from the lower-extremity circulatory beds, thereby increasing cerebral blood flow. [707][708][709][710][711][712][713][714][715] This evidence generated the development of a catheter-based device with 2 balloons near its distal tip placed in the infrarenal and suprarenal positions in the descending aorta (NeuroFlo device; CoAxia, Maple Grove, MN). After insertion via the femoral artery, the balloons are inflated sequentially up to ≈70% of the diameter of the aortic lumen over a period of 45 minutes to an hour, followed by removal.…”
Section: Mechanical Flow Augmentationmentioning
confidence: 99%
“…In a previous study we demonstrated that the thermodilution technique is reliable for measuring CO during thoracic aortic XC [9] . The basic mechanism behind the increase in CO could be volume displacement from the splanchnic circulation to the relatively non-compliant upper part of the body, increasing preload and activating the Frank-Starling mechanism [10] . Another contributing mechanism for the increase in CO is probably a stimulation of the sympathetic nervous system due to ischemia distal to the aortic clamp, with increased release of catecholamines [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…First, mechanical occlusion of the aorta directly increases cardiac afterload whereas activation of the sympathetic nervous system and the RAS results in increased arteriolar vasomotor tone and myocardial contractility. Second, using radioisotopic techniques, it has been shown that blood volume is redistributed from the lower body to the more compliant splanchnic compartment [17]. Third, decreased right ventricular end-diastolic volume has been reported, despite unchanged cardiac filling pressures, suggesting lower cardiac preload associated with reduced ventricular diastolic compliance [18].…”
Section: Discussionmentioning
confidence: 99%